2018
DOI: 10.1111/1750-3841.14221
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Volatiles and Carotenoid Degradation Compounds in Red Pepper Fermented by Lactobacillus parabuchneri

Abstract: This study investigated the changes of volatiles and carotenoids degradation compounds in fermented red pepper inoculated with Lactobacillus parabuchneri during fermentation. These results could be used to improve the quality of red pepper-based products and in the development of certain fermented foods, including Gochujang (fermented red pepper paste) and kimchi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Statistically significant differences between the data were determined using the Duncan multiple comparison test (P < 0.05; Lee, Lee, Cho, Kim, & Kim, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant differences between the data were determined using the Duncan multiple comparison test (P < 0.05; Lee, Lee, Cho, Kim, & Kim, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous report indicated that the contents of terpenes were higher in fermented peppers for 12 days. [12] The differences in trend may due to the different raw materials and fermentation method used. Terpenes occupied a great part of the multiple compounds and are the most variegated class in natural plants, and they exist in a glycoconjugated form in some fruits and vegetables.…”
Section: Volatile Compounds In Fermented-chopped Peppermentioning
confidence: 99%
“…Most of them have been reported previously in different fresh varieties of chilli peppers. 6,7,21 The production of volatile compounds in each Guajillo sauce depended on fermentation time and inoculated yeast as shown in Supporting Information, Table S1. While, the evaluation of the ability of the yeasts to generate volatile compounds at the end of the fermentation (fourth day) was done by PCA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among all the alcohols identified in the fermented sauces (Table 1), five of them (2-methyl-1-butanol, 3-methyl-2-buten-1-ol, 3-ethoxy-1-propanol, 6-methyl-5-hepten-2-ol and benzylalcohol) have not been reported in the fermentation of chilli peppers before. 8,[21][22][23] Moreover, 6-methyl-5-hepten-2-ol and benzylalcohol have been (A) (B) Figure 2. Loadings of the first two principal components (PC1-PC2) of Guajillo fermented sauce at the end of the fermentation (fourth day) (A), and volatile compounds produced (B).…”
Section: Evolution Of Volatile Compounds During Fermentationmentioning
confidence: 99%